Prevalence of stress incontinence in nulliparous elite trampolinists - Eliasson, K.; Larsson, T.; Mattsson, E. (Scandinavian Journal of Medicine & Science in Sports, 2002)
During trampoline jumping the pelvic floor is exposed to high forces. There has been a general belief that physically fit women have a strong pelvic floor as a result of their regular training, thus preventing urinary incontinence. The aim of this study was to survey the prevalence of stress urinary incontinence in female elite trampolinists. The prevalence of urinary incontinence was assessed by a questionnaire, sent to all 35 elite trampolinists (mean age 15, range 12-22 years) in Sweden. Eighty percent of the trampolinists reported involuntary urinary leakage, but only during trampoline training. The leakage started after 2.5 (range 1-4) years of training. Age (P < 0.001), duration of training (P = 0.04), and training frequency (P = 0.01) were significantly associated with leakage. All women above 15 years of age (n = 23) reported urinary leakage (P < 0.001). Eighteen incontinent women continued the study and their leakage was verified by a pad test. The leakage averaged 28 g during a jump session. The muscle strength was measured with perineometry in 10 women and showed good strength in the pelvic floor muscles.